Quality of life of people living with HIV/AIDS attending antiretroviral clinic in the center of excellence in HIV care in India - Sarkar, Trinath (J Educ Health Promot, 2019)
INTRODUCTION: HIV/AIDS is a serious challenge globally. A plethora of morbidities due to crippling immune system reduces quality of life (QOL). The advent of highly active antiretroviral treatment has changed this deadly disease to a chronic manageable illness with focus shifting from fighting virus to ensuring a good QOL. OBJECTIVE: To assess the QOL among people living with HIV/AIDS (PLHA) and factors influencing, if any in Indian setting. MATERIALS AND METHODS: An institutional-based cross-sectional study was carried out among 220 PLHA (male >15 years) attending Anti-Retroviral Therapy Centre of the center of excellence in HIV care in India (Calcutta School of Tropical Medicine, Kolkata) from May 2012 to April 2013. QOL was assessed using WHO-QOL-BREF questionnaire from January 2013 to December 2013. Statistical analysis was done using SPSS version 16; multivariate logistic regression was computed with adjusted odds ratio in 95% confidence interval; P < 0.05 was considered statistically significant. RESULTS: In this study, all 220 PLHA men participated (response rate 96.5%) where more than half (55.5%) participants rated their QOL as neither poor nor good; only 28.2% replied good. One-third (38.6%) were dissatisfied while only one-fifth (19.1%) satisfied and 41.4% mentioned neither satisfied nor dissatisfied with their health. Mean score ± standard deviation on various domains and facets of WHOQOL-BREF were physical health score 56.2 ± 9.8, psychological health 63.1 ± 8.7, social relationship 48.9 ± 14.8, and environmental health 51.3 ± 13.7. CONCLUSION: PLHA had good QOL on psychological, physical, and environmental domain that reflects better services provided at Calcutta School of Tropical Medicine (CSTM), Kolkata, but they scored poorly in social relationship domain, which may be suggestive of ineffective social services network. This study concludes that increase existing social and emotional support with innovation should be implemented to improve their QOL.